The Effect of E-Wom and Consumer Trust on Purchase Decisions With Brand Image as Mediating Variable: Case Study of Indomie Reviewed By Influencer Tasyi Athasyia - Aqilah, Tasya; Irawan , Hery; Usman , Osly (Golden Ratio of Data in Summary, 2025)
The purpose of this study is to examine the relationship between electronic word-of-mouth (eWOM), customer trust in influencers, and purchasing decisions, with Brand Image as a mediator. The author of this study used SmartPLS 4 with a quantitative analysis method. The sample size was 110 people, with the criteria of followers of influencer Tasyi Athasyia and having tried Indomie products. In the results of this study, eWOM does not directly influence purchasing decisions. Consumer trust in influencers influences purchasing decisions. Brand Image can mediate the influence of E-WoM and trust in influencers on purchasing decisions, which means that brand image plays an important role in bridging the influence of communication and consumer trust in determining the final purchasing decision.